Linearity of Soil Moisture in Residential Plants Using Soil moisture sensor YL-69 - Vresdian, Devan Junesco; Pratama, Legenda Prameswono; Trisnaaji, Pius Adrian; Setyono, Rizka Sabila; Jaharadak, Adam Amril; Al-yousif, Shahad (Eksergi, 2024)
Planting media for plants is very important because various kinds of ornamental plants used in housing can grow well according to the needs of their respective conditions. Soil moisture is generally defined as the water contained on the unsaturated soil surface of the Earth. Soil moisture has an influence on the level of moisture needed by plants. The use of soil moisture sensor YL-69s is very popular, especially in the last 2 - 3 decades, where these sensors can review soil moisture and soil conditions in percentage form. However, how can the value of the soil moisture sensor YL-69 itself represent actual conditions? For this reason, a design was carried out with the aim of seeing the linearity value of the sensor. In the overall test the average error value produced has reached less than 3%. In this study, "Nor" conditioning needs to be developed again to further specify whether the plant's moisture needs require a separate percentage to reduce the margin gap that appears at the transition between dry and wet conditions. In this study, using the YL-69 soil moisture sensor produced an error value up to 6.16%, especially in the "Nor" condition with a conditioning difference of 13%.